Avaliação da qualidade de vida relacionada à saúde de pessoas com insuficiência renal crônica em hemodiálise no município de João Pessoa-PB - Melo, Bruna Taisa Nóbrega (2018)
Chronic renal failure (CRF) is the progressive and irreversible loss of renal function. Hemodialysis (HD) is the most used therapy for the treatment of the disease, using a dialyzer or a special filter to remove the impurities that the kidneys could not excrete. The healthrelated quality of life (HRQOL) of people with CRF is affected, since treatment and disease compromise the patients' functional capacity. The objective of this study was to evaluate the HRQOL of people treated at two dialysis units in the city of João Pessoa-PB using the Kidney Disease Quality of Life (KDQOL-SFTM) instrument. The research had a cross-sectional, quantitative approach and descriptive analysis, performed with a sample of 140 patients attended at the clinic of Nefrological Services Fiúza Chaves (NEFRUZA) and at the Unit of Renal Diseases (UNIRIM). The hierarchical log-linear statistical model was used to identify the factors that influence QoL and subsidize decision making. The percentage of female subjects (54.1%) showed that the greater the age, the lower the proportion of patients in HD (60 to 70 years - 13.3%). the average family income was 1 to 3 minimum wages (83.7%) and the schooling level was the fundamental incompleteness (37.8%). As for the treatment time variable, the interval of less than one year of dialysis therapy was predominant (35.7%) and the most prevalent baseline pathology was systemic arterial hypertension (SAH) (75.5%), followed by diabetes mellitus (DM) (19.4%). In the analysis of the variables related to the KDQOL-SFTM instrument that evaluated the QOL, the lowest percentages were observed in the domains: renal disease weight (45.60), occupational activity (11.73), physical performance (33.67) and emotional performance (35, 03). The best scores were obtained in the domains of sexual function (83,24) and encouragement of the dialysis team (82,53). In the application of the log-linear hierarchical model, it was observed that people with DM as basic pathology present a shorter treatment time and worse physical and mental condition than individuals who do not present the pathology. The hierarchical log-linear model developed showed that it can be used as a reference to evaluate QOL and to identify which factors affect the QoL of these people. As the physical part of people in HD was the most affected, it is demonstrated that the professional physiotherapist becomes important in the dialysis centers during the procedure, since the physiotherapy helps in the delay of the pathology, as well as in the performance of the activities of the day to day and in the improvement of the complications resulting from CRF. We identified some risk factors for the reduction of QoL that can be avoided or controlled through planning actions aimed at the prevention and control of CRI.